Recent Understanding of Pathogenesis, and Management Strategies of Asthma: A Literature Review - Adiputra, Ramdhan; Prawiragara, Fachrizal Arfani (Journal of Diverse Medical Research: Medicosphere, 2024)
ABSTRACTAsthma is a chronic inflammatory disease of the airways triggered by an immune response involving Th22 cells and group 3 innate lymphoid cells (ILC2). This disease is divided into two main endotypes: type 2-high, characterized by eosinophilic inflammation and a good response to corticosteroids; and type 2-low, associated with neutrophilic inflammation and a response to non-type 2 cytokines. The aim of this literature review is to examine the literature focusing on the immunology of asthma, its pathogenesis, biomarkers, genetics, epigenetics, and management.           Methods. The literature used included searches in several databases such as Google Scholar and PubMed using keywords relevant to the topic. The results of the review indicate that type 2-high asthma responds well to corticosteroid therapy, whereas type 2-low asthma requires treatment approaches targeting non-type 2 cytokines. Biomarker-based approaches are becoming crucial in asthma management, with studies showing that plant-based diets and vitamin D intake may play a role in controlling asthma.        Conclusion. A deeper understanding of asthma endotypes and associated biomarkers is vital in developing more personalized and effective treatment strategies. Keywords. asthma, endotype, immunology, biomarkers